Assessment of anthelmintic costs to control helminthosis in horses - E. G. Kalugina; O. A. Stolbova (Российский паразитологический журнал, 2025)
The purpose of the research is to assess and economically justify the use of anthelmintics against helminthosis in horses.Materials and methods. The activity of the anthelmintic action of drugs against helminthosis in horses was studied, and a comparative analysis and cost calculation were performed in 2017 to 2025. One hundred and seventy-six Orlov, Russian trotting, Trakehner, Budyonny, Akhal-Teke, English Sport and local horses of different age and gender category, use, and type were examined. The results were processed statistically using Statistica 6.1 and Microsoft Excel software.Results and discussion. It was found that a highly effective and least expensive drug used against helminthosis in horses is a Gelmioks composition form that is advantageous in the composition form (no need for additional labor and time costs to calculate a dose per animal) and ease of use.